Albumin nanoparticle encapsulation of potent cytotoxic therapeutics shows sustained drug release and alleviates cancer drug toxicity. Issue 17 (14th February 2017) - Wang, Hangxiang; Wu, Jiaping; Xu, Li; Xie, Ke; Chen, Chao; Dong, Yuehan
Abstract : We present novel HSA-based nanoassemblies for the formulation of highly potent cytotoxic therapeutic drugs such as maytansinoid DM1. Abstract : We here provide the first report on the construction of nanoparticles formulating highly potent cytotoxic therapeutics using albumin. Maytansinoid DM1 can be efficiently integrated into albumin nanoparticles, resulting in remarkable alleviation of in vivo drug toxicity and expanding the repertoire of albumin technology available for cancer therapy.